2010
DOI: 10.1021/bi902001a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Inhibition of the FabV Enoyl-ACP Reductase from Burkholderia mallei

Abstract: Enoyl-ACP reductases catalyze the final step in the elongation cycle of the bacterial fatty acid biosynthesis (FAS-II) pathway. Currently four distinct enoyl-ACP reductases have been identified, which are the products of the fabI, fabL, fabK and fabV genes. The FabV enoyl-ACP reductase is the most recent member of this enzyme class and was originally identified in Vibrio cholerae by Cronan and coworkers [Massengo-Tiasse and Cronan (2008) Vibrio cholerae FabV defines a new class of enoyl-acyl carrier protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 50 publications
6
52
1
Order By: Relevance
“…Although the enol form of PT191 displays a similar putative binding geometry as PT179 (supplemental Fig. S1) and more closely resembles the potent diphenyl ether PT04 (31, 66), the increased desolvation costs (23,24,29,81). Residues that are likely responsible for the unique NADPH specificity, enhanced mobility (6), and enlarged binding pocket of saFabI are indicated by magenta, black, and red stars, respectively.…”
Section: -Pyridone Pt166 Is a Potent Fabi Inhibitor With Extended Spmentioning
confidence: 98%
“…Although the enol form of PT191 displays a similar putative binding geometry as PT179 (supplemental Fig. S1) and more closely resembles the potent diphenyl ether PT04 (31, 66), the increased desolvation costs (23,24,29,81). Residues that are likely responsible for the unique NADPH specificity, enhanced mobility (6), and enlarged binding pocket of saFabI are indicated by magenta, black, and red stars, respectively.…”
Section: -Pyridone Pt166 Is a Potent Fabi Inhibitor With Extended Spmentioning
confidence: 98%
“…There are four known isoforms of enoyl-ACP reductases, FabI, FabV, FabK, and FabL (31)(32)(33)(34), and bioinformatics has identified that Burkholderia species carry genes that encode both FabI (BP1026B_I1187 and BP1026B_II0795) and FabV (BP1026B_ I1988) enoyl-ACP reductases. To begin to assess the possible role of each of the enoyl-ACP reductases, we performed enzymatic and in vitro and in vivo transcriptional analyses.…”
mentioning
confidence: 99%
“…The loss of interaction between residue 245 and the backbone could result in a loss of catalytic efficiency due to improper positioning of Y235. Mutation of that K245 to methionine in bmFabV has been shown to result in a 10-fold increase in K M [Lu and Tonge, 2010]. In contrast to other FabV homologs, ucFabV contains a glutamate instead of lysine at position 245.…”
Section: Resultsmentioning
confidence: 99%
“…These residues, corresponding to Y156 and K163 in FabI and Y235 and K244 in ucFabV, are likely necessary to stabilize the negatively charged reaction intermediate [Baldock et al, 1998]. Other groups have demonstrated that mutating the lysine to alanine within the YX n K motif in homologous enoyl reductases abolishes the ability of the protein to act as a reductase [Lu and Tonge, 2010;Parikh et al, 1999]. To test whether this residue is important for both triclosan resistance and reductase activity in ucFabV, we mutated lysine 244 to alanine and assayed for the ability of the mutant protein to confer reduced triclosan susceptibility on E. coli ( table 1 ).…”
Section: Resultsmentioning
confidence: 99%